Factors Affecting Body Image Distortion in Adolescents - Eun-Ha Jung; Mi-Kyoung Jun (MDPI AG, 2022)
Body image distortion is an important problem in physical and psychological health in adolescents. This study examined the factors affecting body image distortion in Korean adolescents. A Rao-Scott χ2 test and a complex samples logistic regression was conducted using the statistics from the 17th (2021) Korea Youth Risk Behavior Web-based Survey. The study sample included 41,124 middle and high school students. There was a difference in the presence or absence of body image distortion according to the subject's gender, school grade, school achievement, and economic status (p < 0.001). Approximately 49.5% of subjects with body image distortion had tried to lose weight, but there were few cases where they attempted to lose weight through physical activities, such as moderate physical activity (22.8%), vigorous physical activity (23.3%), and muscle physical activity (23.9%) (p < 0.001). The group with body image distortion was 1.77 times more likely to sit for more than four hours a day on average (p < 0.001). To prevent various factors influencing the distortion of the adolescent's body image, the development of a systematic intervention program for forming no distortion of adolescents' body image is required.